PENGARUH PEMBERIAN BOKASHI KAMBING DAN PUPUK NPK MUTIARA 16:16:16 TERHADAP PERTUMBUHAN DAN HASIL TANAMAN KEDELAI ( Glycine max (L.) Merrill ) VARIETAS GROBOGAN: pupuk bokashi kambing, NPK Mutiara 16:16:16, kedelai - Cahyono, Ajii Cahyono; Sumarmi, Sumarmi; Bahri, Saiful (innofarm, 2023)
Research title "The Influence of Bokashi Goat Fertilizer and NPK Mutiara 16:16:16 Fertilizer on the Growth and Yield of Soybean Plants (Glycine Max (L.) Merrill)". The of purpose this study was to analyze the effect of Bokashi Goat fertilizer and NPK Mutiara 16:16:16 fertilizer on the growth and yield of soybean plants. The was research out from carried November 9 2022 to January 28 2023 the at Tohudan Horticultural Seed Garden, Colomadu District, Karanganyar Regency. In this study, RAKL was used which consisted of 2 treatment factors, namely Goat Bokashi fertilizer (B) which consisted of 4 levels, namely B0 (control), N1: 1.28 kg/plot, N2: 2.56 kg/plot, N3: 3, 84 kg/plot, and NPK Mutiara 16:16:16 fertilizer consisting of 4 levels namely N0 (control), N1: 2.4 g per plant, N2: 4.8 g/plant, N3: 7.2 g/plant plant. Based on these two factors, 16 treatment combinations were obtained, each of which was repeated 3 times. The results showed that the treatment dose of goat bokashi fertilizer was 3.84 kg per plot and the dose of NPK Mutiara fertilizer was 16:16:16 0 g/plant, goat bokashi fertilizer was 3.84 kg per plot and the dose of NPK Mutiara fertilizer was 16:16:16 2 .4 g/plant, goat bokashi fertilizer 3.84 kg/plot and a dose of NPK Mutiara 16:16:16 4.8 g/plant, and goat bokashi fertilizer 3.84 kg/plot and a dose of NPK Mutiara 16:16 :16 7.2 g/plant, gave the best results at a plant height of 98.34 cm and a weight of 100 seeds of 28.67 grams. While 3.84 kg perplot and the dose of NPK Mutiara 16:16:16 7.2 g/plant gave the best results on the number of leaves 91.38, the number of flowers 22.73 stalks, the number of fruitful pods 116.19, the number seed 127.04 grains, wet pod weight 455.03 grams, dry seed weight 124.65 grams.